Losing access to the second language and its effect on executive function development in childhood: The case of 'returnees'. (August 2020) - Kubota, Maki; Chevalier, Nicolas; Sorace, Antonella
Abstract: This study examined how relative language proficiency and exposure influence the development of executive function (EF) in 7–12 year-old bilingual 'returnee' children. Returnees are children of immigrant families who were immersed in an environment where their second language (L2; English) was the majority societal language and returned to their native language (L1; Japanese) environment after the period of prolonged, naturalistic L2 exposure. Targeting this population allows us to address the question of how the loss of opportunities to engage in bilingual activities may longitudinally affect EF development. We administered EF inhibition and monitoring/updating skills tasks shortly after the children's return to their L1 environment and again one year later. The results showed that the amount of reduction in L2 exposure (i.e., the difference in L2 exposure when they lived in an L2 majority language environment vs. back in the L1 environment) affected children's monitoring and updating abilities. The greater reduction the children experienced in L2 exposure, the smaller their improvement was on the updating task in the second interval. The finding suggests that losing access to one's L2, that is, less active bilingualism is associated with attenuated effects in EF development. Highlights: Losing access to the second language (L2) affects executive function development. Greater reduction in L2 exposure contributed to smaller improvement in monitoring. Proficiency did not affect executive function development in childhood.